Measuring of Non-Adherence of Epilepsy Patients to their Medication and its Relationship to their Beliefs about the Disease, and the Frequency of Seizures: A Comparative Study between Epilepsy Patients in Saudi Arabia and Egypt - Madiha Rabie Mahmoud, Hialah Abdalluh Alenazi, Manahel Salem Almutairi, Bayan Sulaiman Alblowi, Osama Gad Abdelaziz, Hager Mohamed Abdelhady, Sherif Gad Abdelaziz (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Medication adherence and believes are crucial to achieving the desired goal of therapy in epileptic patient. Anti-epileptic drugs (AED) are the primary therapeutic modes for epileptic patients and have been demonstrated to control seizure, which decreases morbidity and mortality associated with epilepsy. Our aim is assessment of patient’s non-adherence to anti-epileptic drugs among Saudis and Egyptians, and evaluation of the association between patient beliefs about the disease and the frequency of seizures. Methodology: A cross-sectional study was carried out using online questionnaire among patients with epilepsy in neurology clinics either in Saudi Arabia (KSA) or Egypt. Medication adherence was assessed using a self-reported questionnaire which was designed by the authors with reference to relevant literature. The questionnaire includes patients’ socio-demographic, types, and causes of epilepsy, causes of poor adherence to antiepileptic drugs and belief of patients about epilepsy. All variables were calculated using frequencies and percentages. Results: The prevalence of non-adherence was high among epileptic Saudi patients (52.3%) compared to Egyptians (36.6%). It was reported that older age, female gender, high educational level, high family income significantly increased the patient adherence to AED, while marital and employment status didn’t. Many factors causing poor adherence were forgetfulness, polypharmacy, medication complexity, feeling bad or better which more pronounced among Saudis than Egyptians. Conclusion: Evaluation of medication adherence and improvement of the belief about the importance of medication and identification of factors affecting adherence to treatment is mandatory to reduce seizure frequency, so we recommend educational programs to enhance the patients’ belief about their medication to improve medication adherence presented by the healthcare providers.